2020
DOI: 10.1002/phar.2409
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Crizanlizumab: A New Parenteral Option to Reduce Vaso‐occlusive Pain Crises in Patients with Sickle Cell Disease

Abstract: Hydroxyurea, indicated for managing sickle cell anemia (SCA), and L-glutamine, indicated for treating sickle cell disease (SCD), were the only pharmacotherapeutic options in this patient population before the approval of crizanlizumab by the U.S. Food and Drug Administration in November 2019 to reduce vaso-occlusive crisis (VOC) frequency. This article reviews the evidence pertaining to crizanlizumab in SCD by searching records in Medline, Embase, and International Pharmaceutical Abstracts. Crizanlizumab, a P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…34,35 A post hoc subgroup analysis and a retrospective trial (SUCCESSOR trial) assessed the efficacy of crizanlizumab, using both the data set from the same original SUSTAIN trial and data corroborating the activity of high-dose crizanlizumab at preventing VOEs. [35][36][37] These findings led to the US Food and Drug Administration (FDA) approval of crizanlizumab for the prevention of VOEs in patients with SCD of all genotypes who are >16 years of age. 31 In the subgroup analysis, patients who received only high-dose crizanlizumab had a lower annual crisis rate than those who received crizanlizumab with concomitant hydroxyurea (difference from placebo: −50.0% vs −32.1%).…”
Section: Sustain Trialmentioning
confidence: 99%
“…34,35 A post hoc subgroup analysis and a retrospective trial (SUCCESSOR trial) assessed the efficacy of crizanlizumab, using both the data set from the same original SUSTAIN trial and data corroborating the activity of high-dose crizanlizumab at preventing VOEs. [35][36][37] These findings led to the US Food and Drug Administration (FDA) approval of crizanlizumab for the prevention of VOEs in patients with SCD of all genotypes who are >16 years of age. 31 In the subgroup analysis, patients who received only high-dose crizanlizumab had a lower annual crisis rate than those who received crizanlizumab with concomitant hydroxyurea (difference from placebo: −50.0% vs −32.1%).…”
Section: Sustain Trialmentioning
confidence: 99%
“…15 Because crizanlizumab affects the recruitment of leukocytes, it is unknown if this affects infection risk. 20…”
Section: Dosing Administration and Safetymentioning
confidence: 99%
“…Crizanlizumab offers an alternative for patients who do not tolerate or fail hydroxyurea. 20 As the SUSTAIN trial included both patients receiving hydroxyurea and those who were not, crizanlizumab may be safely administered as monotherapy or in combination. 14 Crizanlizumab can be used regardless of SCD subtype, as all groups demonstrated benefit from crizanlizumab.…”
Section: Relevance To Patient Care and Clinical Practices And Medication Costmentioning
confidence: 99%
“…P-selectin, an adhesion molecule expressed on activated vascular endothelial cells and platelets, facilitates cell-to-cell and cell-to-endothelium interactions that are involved in the pathogenesis of VOC in SCD. 33 The SUSTAIN trial, a multicenter randomized double blind study, showed that crizanlizumab decreased the incidence of VOC by 45% in patients with or without HU. Crizanlizumab also prolonged the median time to the first and second VOC.…”
Section: Approved Pharmacological Drugs For Scd In Current Clinical Pmentioning
confidence: 99%
“… 34 There are several ongoing clinical trials that are trying to explore crizanlizumab’s safety and efficacy in pediatric patients with SCD. 33 …”
Section: Approved Pharmacological Drugs For Scd In Current Clinical Pmentioning
confidence: 99%